2016
DOI: 10.1039/c5cp03600c
|View full text |Cite
|
Sign up to set email alerts
|

Chemical structures and physical properties of vanadium oxide films modified by single-walled carbon nanotubes

Abstract: A series of vanadium oxide (VOx)-single-walled carbon nanotube (SWCNT) composite films with different SWCNT concentrations were prepared and systematically investigated. The results reveal that after SWCNT addition, the optical absorption and electrical conductivity of VOx are enhanced, but the crystallinity and temperature coefficient of resistance (TCR) are weakened. Consequently, either too low or too high CNT loading will lead to the degradation of the comprehensive properties. In contrast, the VOx-SWCNT c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 40 publications
3
20
0
Order By: Relevance
“…SEM images (Fig. 1) suggest that both MWCNTs and SWCNTs are chemically interacted with VO x , thus modifying the morphology and crystallinity of VO x [3]. Moreover, the interactions between VO x and MWCNTs seem stronger than those between VO x and SWCNTs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…SEM images (Fig. 1) suggest that both MWCNTs and SWCNTs are chemically interacted with VO x , thus modifying the morphology and crystallinity of VO x [3]. Moreover, the interactions between VO x and MWCNTs seem stronger than those between VO x and SWCNTs.…”
Section: Resultsmentioning
confidence: 99%
“…With the rapid development of devices, further improvements on the chemical structures and physical properties of such materials are required. One of the most efficient ways to adjust the properties of VO x is preparing composite materials, among which VO x -CNT composites have drawn considerable attentions [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…It is known that carbon nanotube (CNT) and graphene (G) are two of the most important and widelyapplied nanomaterials for enhancing the electrical properties of organic and inorganic materials (Geim and Novoselov 2007;Bai et al 2011;Wang et al 2015a). In fact, the optical properties can also be modified by CNT or G, owing to their unique optical properties and inherent geometric structures (He et al 2015;Chen et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Up to now, many literatures about modifications of the electrical and/or optical properties of organic or inorganic materials by CNT or G have been previously reported (He et al 2015;Chen et al 2018;Li et al 2011;Zhang et al 2010). For example, He and co-workers reported that both the electrical conductivity and infrared absorption of VO x film can be efficiently enhanced by CNTs (He et al 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation